Multicultural Education: Components and Necessities - Ghimire, Tulasi Ram (KMC Research Journal, 2020)
The educational systems of different countries have committed to addressing/respond to the existing racial, ethnic, linguistic, and cultural variations. Multicultural education is an approach adopted to respond to cultural diversity in society. This paper aims at analyzing the concept of multicultural education and identifies its components and necessities in so doing, the author employed qualitative and content analysis. To collect the required information, all available sources of multicultural education in print and electronic libraries (valid databases) were used and were analyzed using the inductive category. The findings of this research, along with specifying the concept of multicultural education, also showed that attention to multicultural curriculum, in the global and national situations is an inevitable necessity. At the end of the study, the components and needs of multicultural education were identified. In short, acceptance of diversity and plurality, peaceful coexistence respect to educational justice, flexibility in educational programmes, variety in methods, variety in using educational materials, using a variety of evaluation methods, training of human resources, who promote and strengthen the differences, the human tendency to create social trends rather than a specific, positive attitude to different cultures, helping to develop a positive self-concept, to protection of minority languages, strengthening intercultural cross-cultural communication and so on can be ways to ensure multicultural education.